Strategies to minimize intraoperative blood loss during major surgery. Issue 2 (5th January 2020) - Shah, A.; Palmer, A. J. R.; Klein, A. A.
Abstract : Background: Reducing operative blood loss improves patient outcomes and reduces healthcare costs. The aim of this article was to review current surgical, anaesthetic and haemostatic intraoperative blood conservation strategies. Methods: This narrative review was based on a literature search of relevant databases up to 31 July 2019 for publications relevant to reducing blood loss in the surgical patient. Results: Interventions can begin early in the preoperative phase through identification of patients at high risk of bleeding. Directly acting anticoagulants can be stopped 48 h before most surgery in the presence of normal renal function. Aspirin can be continued for most procedures. Intraoperative cell salvage is recommended when anticipated blood loss is greater than 500 ml and this can be continued after surgery in certain situations. Tranexamic acid is safe, cheap and effective, and routine administration is recommended when anticipated blood loss is high. However, the optimal dose, timing and route of administration remain unclear. The use of topical agents, tourniquet and drains remains at the discretion of the surgeon. Anaesthetic techniques include correct patient positioning, avoidance of hypothermia and regional anaesthesia. Permissive hypotension may be beneficial in selected patients. Promising haemostatic strategies include use of pharmacological agents such as desmopressin, prothrombin complex concentrate and fibrinogen concentrate, and use of viscoelastic haemostatic assays. Conclusion: Reducing perioperative blood loss requires a multimodal and multidisciplinary approach. Although high‐quality evidence exists in certain areas, the overall evidence base for reducing intraoperative blood loss remains limited. Abstract : Reducing perioperative blood loss is a key component of patient blood management. Multimodal surgical, anaesthetic and haemostatic interventions are available, and implementation requires a multidisciplinary approach. Things that work to reduce bleeding A video abstract is available at https://youtu.be/Lc7YDxMy2is Abstract : Antecedentes: La reducción de la pérdida hemática operatoria mejora los resultados y reduce los costes sanitarios. El objetivo de este artículo es revisar las estrategias actuales intraoperatorias quirúrgicas, anestésicas y hemostáticas de ahorro de sangre. Métodos: Revisión descriptiva basada en publicaciones destacadas que analizaban la forma de reducir la pérdida de sangre en el paciente quirúrgico, seleccionadas a partir de una búsqueda bibliográfica en bases de datos relevantes hasta el 31 de julio de 2019. Resultados: Las intervenciones se pueden iniciar precozmente en el período preoperatorio a través de la identificación de pacientes con elevado riesgo de hemorragia. Se pueden suspender los anticoagulantes de acción directa 48 horas antes de la mayoría de las operaciones quirúrgicas si la función renal es normal. Se puede continuar la administración de aspirina en la mayoría de las intervenciones. En el período intraoperatorio, se recomienda el uso de rescate celular cuando la pérdida de sangre prevista es superior a 500 ml y este método se puede continuar después de la operación en determinadas situaciones. La administración de ácido tranexámico es segura, barata y eficaz y se recomienda de forma rutinaria cuando la pérdida hemática prevista es alta. Sin embargo, la dosis óptima, el momento y la vía de administración no están bien establecidos. El uso de agentes tópicos, torniquetes y drenajes queda a discreción del cirujano. Las técnicas anestésicas incluyen la correcta posición del paciente, así como evitar la hipotermia y la anestesia regional. La hipotensión controlada puede ser beneficiosa en casos seleccionados. Las estrategias hemostáticas innovadoras incluyen agentes farmacológicos como la desmopresina, los concentrados del complejo de protrombina y concentrados de fibrinógeno, y el uso de hemostáticos viscoelásticos, pero se requiere disponer de evidencia sobre su beneficio. Conclusión: La reducción de la pérdida hemática perioperatoria requiere un enfoque multimodal y multidisciplinario. Aunque existe evidencia de alta calidad en ciertas áreas, la evidencia general para reducir la pérdida hemática intraoperatoria sigue siendo limitada.